1988
DOI: 10.1037/0097-7403.14.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and inhibition in unblocking.

Abstract: In four experiments the nature of learning established with unblocking procedures in the appetitive conditioning of rats was examined. Measures of learning included response topography, effects of selective satiation, and summation and retardation tests of conditioned inhibition. One cue (A) was first paired with either a single unconditioned stimulus event, US1, or a sequence of two events, US1----US2. US2 was either qualitatively similar to (US2-Same) or different from (US2-Diff) US1. Then, a compound of A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
84
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 22 publications
12
84
2
Order By: Relevance
“…However, previous data provide some support for the first of these claims. Holland (1988;Exps. 3 and 4) found that in a number of circumstances, downshifts from a two-reinforcer sequence to a single reinforcer simultaneously produced both excitatory and inhibitory learning about the added cue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous data provide some support for the first of these claims. Holland (1988;Exps. 3 and 4) found that in a number of circumstances, downshifts from a two-reinforcer sequence to a single reinforcer simultaneously produced both excitatory and inhibitory learning about the added cue.…”
Section: Discussionmentioning
confidence: 99%
“…Holland and Gallagher (1993b) found that rats acquired substantial excitatory learning about the added auditory CS, supporting models like Pearce and Hall's (1980). Although some investigations using downshift procedures have revealed inhibitory learning (e.g., Cotton, Goodall, & Mackintosh, 1982;Holland, 1988, Wagner, Mazur, Donegan, & Pfautz, 1980, the frequent observation of substantial excitatory learning (e.g., Bucci, Holland, & Gallagher, 1998;Dickinson, et al, 1976;Dickinson & Mackintosh, 1979;Holland, 1984Holland, , 1988Holland & Gallagher, 1993b) has been a major source of support for the claim that the disconfirmation of reinforcement expectancies can enhance processing of CSs. Indeed, as we discuss later in this article, we have used excitatory learning in unblocking as a tool for investigating brain mechanisms involved in attentional processes such as those specified in the Pearce-Hall (1980) model (Bucci, et al, 1998;Holland & Gallagher, 1993b.…”
mentioning
confidence: 90%
“…First comes evidence from a study of unblocking by reinforcer addition by Holland (1988), in which US2 was qualitatively different from US1 (sucrose solution vs. solid food pellets) and generated a conditioned response with a different response topography, such that, on test, it was possible to determine the nature of learning about the added CS on compound trials. This experiment indicated that the major function of the added US2 was to enhance the development of associations between the added CS and the original reinforcer, US1.…”
mentioning
confidence: 99%
“…Second come demonstrations of excitatory unblocking as a result of the omission of an expected reinforcer (Dickinson et al, 1976;Dickinson & Mackintosh, 1979;Holland, 1984Holland, , 1988. In these studies, trials on which Cue A is followed by US1 and then US2 precede trials on which Cue AB is followed by US1 alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation